Intrathyroidal thyroglossal duct cyst: two interesting cases and review of literature - Prabha, Blessy B.; Rangachari, Vijay; Bhat, Vidya B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The features and presentation of thyroglossal duct cyst as a midline neck swelling are well known. We present two cases of intrathyroidal thyroglossal duct cyst who presented as a classical thyroid nodule. Distinguishing features, clinical work up, management, histopathological findings and literature review are presented. Intra-thyroidal thyroglossal duct cyst masquerading as a thyroid nodule is rare, and should be borne in mind in the differential diagnosis of solitary nodule of thyroid. Preoperative aspiration cytology findings of benign squamous cells should be a pointer towards the presence of intrathyroidal thyroglossal cyst.